BAHASA DALAM KOMUNIKASI GENDER - Machyudin Agung Harahap; Susri Adeni (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
Language is an activity that absolutely must be done in communication.Gender differences affect the language used in communication.Men and women show different languages when communicating in all fields.This is interesting to discuss because gender affects the way or style of language used by men and women.Likewise, the culture that creates gender stereotypes in communication. This article discusses the language differences between men and women in communicating with the aim of describing gender differences in language and cultural stereotypes.